The mask and masked characters in folguedos maranhenses (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This work discusses the use of the mask as an aesthetic, lewd object, sometimes poetic, sometimes contraventive, and about its use during periods of remarkable festivities in the popular culture of the State of Maranhão. It seeks to establish a brief investigation about the symbology of such objects in the aspects of laughter and the grotesque. It is also sought to establish a brief understanding of how and when this mask object and its use in folguedos may have been considered harmful or a victim of a retrograde political position. Overcoming possible divergences, it can be found largely as a member of typological compositions of characters, from the construction of varied formats and materials and also from the different ways of dressing it.
Keywords: Maranhão; Mask; Folguedo; Popular Culture